Eksplorasi Teknik Shibori Dalam Pengembangan Motif Geometrik Pada Kain Sandang - Insanul Qisti Barriyah; Dharmawati Dewi Pamungkas; BQ. Fatmayanti; Triyono Triyono (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2023)
The motifs on the cloth are increasingly diverse, but can still be developed with various explorations, both materials and techniques. The method in this research is to make observations and study the literature first to get the potential of the shibori technique. There is an opportunity or potential for the shibori technique to be developed further by utilizing various textile techniques. Geometric is a symmetrical and regular formation consisting of several shapes such as rectangles, triangles, circles, rhombuses and many more. Meanwhile, shibori is a color barrier technique originating from Japan. The method used in the exploration of this shibori work is the application of shape and design. The author makes thoughts and observations about the ideas, concepts and techniques that will be used. The author makes designs according to the results that have been observed and thought about, then processed into a batik work using geometric motifs and shibori techniques. keyword: geometric, shibori